Lafoeina longitheca Jaderholm 1904 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Lafoeina longitheca Jäderholm, 1904 (*) Lafoeina longitheca — Hickson & Gravely, 1907: 29, pl. 4 fig. 31; Ritchie, 1913: 10, 25; Peña Cantero et al., 2013: 741, fig. 5g –h. Distribution. Pan-Antarctic (Peña Cantero & Vervoort 2009). In the Ross Sea, known from McMurdo (Hickson & Gravely 1907), Cape Royds (Ritchie 1913) and Tethys Bay (Peña Cantero et al. 2013). ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on pages 25-26, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...